Joint Decision on Integrated Supplier Selection and Stock Control of Inventory System Considering Purchase Discount - Widowati Widowati; Sutrisno Sutrisno; R. Heru Tjahjana (International Journal of Supply Chain Management, 2017)
Stock control and supplier selection are two vital parts on supply chain and management. Integrating these parts by solving them simultaneously is a good idea for cost reducing. Furthermore, if some suppliers give a purchase discount for their product, how to determine the optimal strategy is interesting. In this paper, we propose a mathematical model in a mixed integer quadratic programming with piecewise objective function to determine the optimal strategy for integrated supplier selection and stock control of multiproduct inventory system considering purchase discount. This stock control refers to bring the stock level of each product to a reference level given by decision maker. We formulate the model in two environments which are deterministic where all parameters are known and stochastic where the demand is random. Two numerical experiments are performed to evaluate the model. From the results, the optimal strategy was generated i.e. the optimal product volume purchased from each supplier and the stock level of each product follows the reference level.